Obstacles to the Consumer Protection Dispute Settlement Process Can Not Work Effectively (Case Study of BPSK District of Tangerang) - Pardamean Harahap; Faisal Santiago (International Journal Labs, 2023)
Everyone has been a consumer to fulfill their life needs, both primary and secondary needs in order to obtain goods and services, although not everyone has become a business actor, therefore as a consumer, it is not spared from various problems that may occur such as fraud by business actors, fraud and so on, it is necessary to settle consumer disputes properly and correctly, through the courts and outside the court such as the Consumer Dispute Settlement Agency (BPSK) as a new institution that provides opportunities for consumers and business actors to choose one of three consumer dispute resolution mechanisms, namely: Conciliation, Mediation, and Arbitration. This research uses several methods, namely: first, the literature study consists of (a). types of normative legal research or secondary data document studies; (b). the nature of the research in this study using descriptive analysis research; and (c). the types of data consist of primary legal data, secondary legal data, and tertiary legal materials. The second was to interview two members of the Consumer Dispute Resolution Agency (BPSK) in the Tangerang district and one of the administrators at the BPSK secretariat in the Tangerang district.